The Mummy against the elements and other adventures (Unversal Studios, 2004)
Following a clue the discovered in the diaries of Alexander the Great, The O'Connel family return to ancient Egypt in pursuit of the scrolls of thebes. however - evil awaits them. imhotep uses all of his terrible powers to stop our heroes recovering the scrolls.